ANALISIS PENGARUH RETURN ON ASSET (ROA) DAN NET PROFIT MARGIN (NPM) TERHADAP HARGA SAHAM PADA PERBANKAN YANG TERDAFTAR DI LQ45 - LILIS PUTRIYANI; ARIS MUNANDAR (Universitas Mahasaraswati K. Mataram, 2024)
This research was conducted with the aim of examining the influence of Return On Assets (ROA), Net Proft Margin (NPM) on share prices in banks registered in LQ45 for the 2019 - 2022 period. The data used in this research is based on secondary data in the form of quantitative data. The research instrument used to measure this research uses a table listing the variable indicators Return On Assets (ROA), Net Profit Margin (NPM), and Price Earning Ratio (PER). The population of this research is all banks registered in LQ45 for 28 years, namely from 2019-2022. The samples in this research are 4 years each, so the total sample in this research is 20 years, namely from 2019 to 2022. The sampling technique used in this research is a non-probability sampling technique. The data collection techniques used in this research are documentation and literature study. The documentation intended in this research is financial reports and annual reports for banks registered in LQ45. The data analysis technique in this research is using the classic Assumption Test, Multiple Linear Regression Test, t Test, and F Test. The research results show that the variables Return On Assets (ROA) and Net Profit Margin (NPM) have no effect on stock prices (PER).